1992
DOI: 10.1530/jrf.0.0960187
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of bovine blastocysts obtained by in vitro culture of oocytes matured and fertilized in vitro

Abstract: Two experiments were conducted to assess the viability of bovine blastocysts obtained by in vitro fertilization of oocytes matured in vitro (IVM-IVF) and cryopreserved by vitrification. In Expt 1, the optimal concentrations of glycerol and 1,2-propanediol in the basic medium (modified TCM199) for cooling and warming without formation of ice crystals were determined by plunging the solution into liquid nitrogen and then warming it in a water bath at 15 degrees C; when both glycerol and 1,2-propanediol were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 10 publications
1
27
0
2
Order By: Relevance
“…Fresh-vitro embryos used in the present study were obtained from a commercial supplier and their production details are described elsewhere [11]. Ovaries were obtained from a local abattoir and transported to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh-vitro embryos used in the present study were obtained from a commercial supplier and their production details are described elsewhere [11]. Ovaries were obtained from a local abattoir and transported to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…In attempts to avoid the critical minimum cell volume, common methods for oocyte and zygote vitrification have incorporated at least three-step equilibration processes whereby cells are manually pipetted into subsequently higher levels of permeating CPA concentrations (Kuwayama et al, 2005a(Kuwayama et al, , 2005bPegg, 2010;Smith et al, 2010) allowing the cell to shrink in a specific interval. It has been experimentally demonstrated that the use of a higher number of 'steps' leads to enhanced cryosurvival and developmental outcomes (Kuwayama et al, 1992;Otoi et al, 1998); however, such protocols have not been adopted due to impracticality. The use of an automated, continuously and gradually changing CPA concentration exposure is a logical extension of this previous work, as a continuously gradual change in CPA concentration is fundamentally an 'unlimited amount of steps'.…”
Section: Cryopreservation With Microfluidicsmentioning
confidence: 99%
“…The procedures for in vitro maturation, fertilization and culture of transferred embryos have been described in detail elsewhere 12 . Pregnancy and fetal number were diagnosed around days 30, 45, 60 and 90 by transrectal ultrasonography and confirmed at parturition.…”
Section: Animalsmentioning
confidence: 99%